1970
DOI: 10.1172/jci106331
|View full text |Cite
|
Sign up to set email alerts
|

The demonstration of alternating contractile state in pulsus alternans

Abstract: A B S T R A C T Pulsus alternans was induced in 11anesthetized, open-chest dogs by rapid atrial pacing, and the left ventricular filling characteristics and lengthtension-velocity relationship of alternating beats were compared. The end-diastolic circumferences (circ) of the strong beats were slightly, but significantly, increased over the weak beats (7.3 > 6.9 cm, P < 0.01), confirming that diastolic filling does alternate in pulsus alternans. This alternation in initial fiber length seemed to result from an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1974
1974
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…A variation in contractility between strong and weak had been described by the study of Vmax and Vc~ in open-chest dogs with pulsus alternans obtained by rapid pacing (14) but these beats were not compared to control beats. As compared with the beats preceding the premature ventricular contraction, in hypoxic regions, the strong beats appear as potentiated and the weak beats appear as attenuated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variation in contractility between strong and weak had been described by the study of Vmax and Vc~ in open-chest dogs with pulsus alternans obtained by rapid pacing (14) but these beats were not compared to control beats. As compared with the beats preceding the premature ventricular contraction, in hypoxic regions, the strong beats appear as potentiated and the weak beats appear as attenuated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown (10) that for the same level of inotropic state, endsystolic length is shorter with a decreased systolic pressure; in the weak beats, systolic pressure was lower and % systolic shortening was significantly decreased which indicates thus a decreased inotropic state. In most of the experiments (1,4,8,11,14) pulsus alternans is produced by rapid pacing of the heart which produces by itself a potentiation of contraction (9) which makes difficult the comparison between beats of pulsus alternans and previous beats. A variation in contractility between strong and weak had been described by the study of Vmax and Vc~ in open-chest dogs with pulsus alternans obtained by rapid pacing (14) but these beats were not compared to control beats.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the concept that MP can be induced in a heart in which contractile characteristics (F., L., V.) are time invariant is in contrast with the commonly held explanation that suggests that time variant values for these parameters (Cohn et al, 1967;Noble & Nutter, 1970;McGaughey et al, 1985) cause MP. However, our analysis cannot predict MP of pathologies as emphysema or pericardial tamponade, where values of mechanical or hemodynamic characteristics are time variant.…”
Section: Rmentioning
confidence: 95%
“…Our results provide qualitative and quantitative predictions which can be used for comprehensive experimental design. (Back, 1977;Janz, 1982;Kim et al, 1985;Beyar & Sideman, 1986 (Gleason & Braunwald, 1962;Noble & Nutter, 1970;Guntheroth, 1982;Laskey et al, 1983;McGaugher et al, 1985). Recently, (Adler et al, 1985;Adler & Mahler, 1987) have modeled the beating heart as a dynamical system, using only certain aspects of the heart's functions.…”
mentioning
confidence: 99%
“…10 It also has been demonstrated that when EDV is greater before the strong beat, significant variations in end-diastolic pressure (EDP) 13 Figure 2, we chose slopes of 0.8 and 0.9 to represent the real cases. Obviously, the same conclusions would be obtained if parallel slopes with the exact value of 1, or any other value, were plotted.…”
Section: Effect Of Filling Volume On Sustained Mechanical Altemansmentioning
confidence: 99%